Acrobatic gymnastics: The effect of experience, interpersonal coordination and variability in partner-assisted flight - Leite, I.; Gómez-Landero, L. A.; Ávila-Carvalho, L.; Vilas-Boas, J. P.; Goethel, M.; Conceição, F.; Mochizuki, L. (Journal of Sports Sciences, 2025)
Acrobatic gymnastics demands inter-partner coordination during partner-assisted flights. This work aims to investigate (1) the effect of pair experience on inter-partner coordination and (2) on its variability and (3) the association between the flight phase and coordination modes during a pair task. Twelve pairs of acrobatic gymnasts performed 10 vertical throws in laboratory settings. The position and velocity of the center of mass were used for vector coding analysis to quantify the coordination modes into in-phase, anti-phase, base-phase and top-phase, and continuous relative phase to study the coordination variability. Pairs were grouped by the experience level and the trials by the top gymnast`s height achieved. Results showed that more experienced pairs spend less time moving in-phase, more time in base-phase and use less parallel coordination. Coordination variability was similar between groups, but time-series differed in the time segment of 60.7%-78.7% of the task, during upward motion (p <0.05). Trials that reached a greater height used coordination modes similar to more experienced pairs. These findings suggest that the experience level influences the inter-partner coordination, underscoring the potential for learning and adaptation in less experienced pairs and offering valuable information for training strategies aimed at achieving higher flight phases.